2023
DOI: 10.2516/stet/2022023
|View full text |Cite
|
Sign up to set email alerts
|

NACA2412 airfoil based method for design and aerodynamic analysis of small HAWT using modified BEM approach

Abstract: Efficient utilization of wind energy depends on careful selection and suitable design of Wind Turbine (WT) blades. Small scale Wind Turbines (SWT) normally operate in the low range of Angle of Attack (AoA). This makes the task even more difficult for designing and optimization of WT blades. This article deals with an airfoil based computational approach to design the blade for a standalone small scale Horizontal Axis Wind Turbine (HAWT). A procedure has been proposed to find the important parameters and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Figure 5 shows the twist/chord values determined along the blade length by putting k = 1 in the objective function (Equation ( 14)) and ideal Equations ( 17) and (18). It can be observed that the distributions obtained from the DE 9 International Journal of Energy Research method are similar to the distributions acquired from the ideal equations.…”
Section: Validation Of the Optimizationmentioning
confidence: 74%
See 1 more Smart Citation
“…Figure 5 shows the twist/chord values determined along the blade length by putting k = 1 in the objective function (Equation ( 14)) and ideal Equations ( 17) and (18). It can be observed that the distributions obtained from the DE 9 International Journal of Energy Research method are similar to the distributions acquired from the ideal equations.…”
Section: Validation Of the Optimizationmentioning
confidence: 74%
“…The new designs were capable of generating the same amount of power as the reference turbine but at lower wind speeds, indicating better overall performance. Jha and Saurabh [18] proposed a computational approach for designing blades for SHAWTs operating under wake rotation. The proposed procedure utilized the NACA2412 airfoil and analyzed important parameters to obtain accurate blade design and performance.…”
Section: Introductionmentioning
confidence: 99%